TO WHAT EXTENT TAXONOMY ENGLISH LANGUAGE TEACHING APPLIED BY THE LECTURERS IN TEACHING READING - Abdul Halim (Institut Agama Islam Negeri Kendari, 2015)
AbstractThe objective of this research is to find out the teaching techniques used by lecturers in reading II at the second semester of English Department of Muhammadiyah University of Kendari academic year 2013/2014. This studyused 4 different lecturers who taught in four different classes. The data were gathered through observation, note taking, interviewing, and videotaping. These gathered data were analyzed based Miles and Huberman (1984). The result of the study showed that lecturers mostly used three techniques: controlled, semicontrolled, and free. However, the most prevalent technique used by the lecturers is controlled techniques, and then followed by semi-controlled and free technique respectively. This study revealed two conflicting results. Firstly, most of lecturers who have been the subject of this study believed that controlled technique worked much better compared to semi-controlled and free technique in improving students’ reading comprehension. Secondly, what lecturers believed about their favored teaching technique does not in line with students’ good reading comprehension. Keywords: Lecturers’ technique, Teaching Reading AbstrakTujuan dari penelitian ini adalah untuk mengetahui aspek aspek dari taxonomy English language teaching yang digunakan oleh dosen pada saat mengajar matakuliah reading II pada semester II Jurusan Bahasa Inggris Universitas Muhammadiyah Kendari tahun ajaran 2013/2014. Penelitian ini menggunakan 4 dosen yang berbeda yang diajarkan di empat kelas yang berbeda. Data dikumpulkan melalui observasi, pencatatan, wawancara, dan rekaman video. Data ini dikumpulkan dan kemudian dianalisis berdasarkan Miles dan Huberman (1984). Hasil penelitian menunjukkan bahwa dosen menggunakan tiga teknik: control, semi control, dan free control. Namun, teknik yang paling umum digunakan oleh dosen dikendalikan teknik, dan kemudian diikuti denganteknik semi-dikontrol dan bebas masing-masing. Penelitian ini mengungkapkan dua hasil yang bertentangan. Pertama, sebagian besar dosen yang telah menjadi subyek penelitian ini percaya bahwa teknik terkontrol bekerja jauh lebih baik dibandingkan dengan teknik semi-dikontrol dan bebas dalam meningkatkanpemahaman membaca siswa. Kedua, apa yang dosen percaya tentang teknik pengajaran favorit mereka tidak sejalan dengan baik pemahaman bacaan siswa.Kata Kunci: Teknik Dosen, Mengajar Membaca